Assessment of dentofacial widths in adults with anterior open bite - R Dawal; M S Ravi; P S Murali; C R Soans; Shetty Kaushik (Wolters Kluwer Medknow Publications, 2020)
Context: Anterior open bite is a complex condition involving a combination of various dental and skeletal components in three dimensions. The data on the differences and changes in the transverse relation in individuals with anterior open bite are limited. Aims: To assess the dental arch widths in individuals with anterior open bite using study casts and facial widths using frontal cephalogram and to compare these widths with that of individuals without anterior open bite. Materials and Methods: Eighty adults [40 with and 40 without anterior open bite, mean (standard deviation) age = 20.68 years] were selected. The study group was divided into skeletal (n = 19) and dental (n = 21) open bite groups according to Jarabak's ratio. Posteroanterior cephalograms and study casts were analyzed. Results: The mean width of zygomatic arch (112.18 mm) and condylar region (100.55 mm) in the control group was significantly higher (P < 0.05). The mean gonial width in the skeletal open bite group (81.143 mm) was significantly (P < 0.05) lesser than the dental open bite group (84.842). The maxillary intercanine width for the skeletal open bite group (36.48 mm) was significantly (P < 0.01) higher than that of the dental open bite group (34.26 mm). Conclusion: A transverse deficiency was seen in in the zygomatic and condylar regions in adults with anterior open bite. Individuals with a skeletal open bite showed a narrow gonial and wider maxillary intercanine width compared with individuals with dental open bite.